Kevalidan E-Modul Statistika Menggunakan Model Pembelajaran Jucama - Sari, Cindy Nadriana; Efriani, Arvin; Arifin, Sujinal (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
This study aims to produce a math learning e-module based on the Jucama learning model on valid SMP class VIII statistics material. This research was development research with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were eighth grade students at one of the Palembang State Middle Schools. Data collection techniques used were interviews and validation sheets. Validity data was obtained based on comments and suggestions from the validators. The results of this study indicate that the developed e-module is declared valid based on the validator's comments and suggestions.